2000
DOI: 10.1063/1.372279
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering from Ge nanostructures grown on Si substrates: Power and limitations

Abstract: The analysis of Raman spectra obtained for different germanium nanostructures grown on silicon substrates is presented. Comparison of these spectra with a Raman spectrum of a silicon wafer reveals a one-to-one correspondence of features located around 229, 300, and 435 cm−1. It is argued that the peaks observed at these frequencies and often ascribed to Ge nanostructures are, in fact, coming from the Si substrate. The erroneous ascription of the peaks makes the corresponding conclusions incorrect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(54 citation statements)
references
References 24 publications
2
49
0
3
Order By: Relevance
“…The Raman spectra of the multilayer films deposited on GaAs and (100) Si show a sharp peak around 300 cm −1 , which is consistent with fully crystallized Ge layers [27,28]. It has been shown that a peak at 300 cm −1 could also originate from Si substrates [29], but in our case, a comparison between a Si substrate and a Si substrate capped with a thin epitaxial Ge layer showed that no signal from the Si substrate alone at 300 cm −1 was distinguishable whereas a very sharp peak would appear in the presence of this thin Ge layer. On the other hand, the film deposited on (111) c-Si substrate displays a shoulder towards lower wavenumbers, indicating that the film is partially crystallized and contains an amorphous phase, since the hydrogenated amorphous Ge has a TO mode at 278 cm −1 [28].…”
Section: Resultssupporting
confidence: 52%
“…The Raman spectra of the multilayer films deposited on GaAs and (100) Si show a sharp peak around 300 cm −1 , which is consistent with fully crystallized Ge layers [27,28]. It has been shown that a peak at 300 cm −1 could also originate from Si substrates [29], but in our case, a comparison between a Si substrate and a Si substrate capped with a thin epitaxial Ge layer showed that no signal from the Si substrate alone at 300 cm −1 was distinguishable whereas a very sharp peak would appear in the presence of this thin Ge layer. On the other hand, the film deposited on (111) c-Si substrate displays a shoulder towards lower wavenumbers, indicating that the film is partially crystallized and contains an amorphous phase, since the hydrogenated amorphous Ge has a TO mode at 278 cm −1 [28].…”
Section: Resultssupporting
confidence: 52%
“…The Raman spectra of all of these samples contained two distinct phonon peaks, which could be attributed to a Ge-Ge phonon mode (≈300 cm −1 ) and Si-Ge phonon mode (≈415 cm −1 ) respectively. 21 The Raman spectrum of the as-deposited sample also exhibited a broad peak at ≈270 cm −1 , which could be attributed to amorphous Ge. 22 As can be seen, the amorphous Ge peak diminished and the Ge-Ge peak got narrower with increasing number of accumulated laser shots (decreasing scan speed).…”
Section: -4mentioning
confidence: 98%
“…The values of I Ge-Ge /I Si-Ge for the QD samples produced at different conditions are comparable to that for self-assembled QDs grown in SK mode. 21 This means that the production of Ge/Si QDs by using SPLA does not result in a stronger intermixing than self-assembled QDs produced with SK growth, thus equally promising for applications in this respect. The Ge-Ge Raman peak should shift to the red side or the blue side when there is compressive or tensile strain in the Ge layer.…”
Section: -4mentioning
confidence: 99%
“…In Ref. [20] it was argued that both features at 300 cm −1 and 430 cm −1 in such samples can be two-photon Raman peaks from the Si substrate on which the SiO 2 layer is grown. In our samples, the intensities of these peaks change with annealing, which is not expected if they arise from Si substrate (the intensity of the Si peak at 522 cm −1 remains unchanged with annealing).…”
Section: Resultsmentioning
confidence: 99%